1986
DOI: 10.1002/gea.3340010301
|View full text |Cite
|
Sign up to set email alerts
|

Late quaternary environmental history of the southern Levant

Abstract: The Late Quaternary history of northern Sinai and the western Negev is inferred from a number of stratigraphic sequences rich in prehistoric and archaeologic remains. Exposures are abundant along the wadi courses which drain the highlands westward to the Mediterranean. Earliest deposition is represented by coarse, well rounded gravels containing Middle Paleolithic artifacts and is dated to ca. 90,000 to 70,000 B.P. These are overlain by finer grained sands, silts, and clays, ultimately of eolian origin, but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…In earlier work, this was due to a lack of datable material by the methods then available, or to the use of methods that are not appropriate for determining ages of the loess deposits or paleosols [Enzel et al, 2008]. The published chronologies and the rates of dust accretion and erosion that have been inferred from them are based heavily on stratigraphic relations and association with human artifacts, and on radiocarbon analyses of pedogenic calcic nodules [e.g., Yaalon and Dan, 1974;Horowitz, 1979;Issar and Bruins, 1983;Enzel, 1984;Issar et al, 1984;Gerson et al, 1985;Goldberg, 1986;Magaritz, 1986;Gerson and Amit, 1987;Yair and Enzel, 1987;Goodfriend and Magaritz, 1988;Zilberman, 1992;Ben David, 2003]. Only recently have reliable optically stimulated luminescence (OSL) ages been reported for the late Pleistocene loess of the Negev [Avni et al, 2006], but even these ages are on reworked, secondary fluvial loess and not primary loess.…”
Section: Loess In the Negev Desertmentioning
confidence: 99%
“…In earlier work, this was due to a lack of datable material by the methods then available, or to the use of methods that are not appropriate for determining ages of the loess deposits or paleosols [Enzel et al, 2008]. The published chronologies and the rates of dust accretion and erosion that have been inferred from them are based heavily on stratigraphic relations and association with human artifacts, and on radiocarbon analyses of pedogenic calcic nodules [e.g., Yaalon and Dan, 1974;Horowitz, 1979;Issar and Bruins, 1983;Enzel, 1984;Issar et al, 1984;Gerson et al, 1985;Goldberg, 1986;Magaritz, 1986;Gerson and Amit, 1987;Yair and Enzel, 1987;Goodfriend and Magaritz, 1988;Zilberman, 1992;Ben David, 2003]. Only recently have reliable optically stimulated luminescence (OSL) ages been reported for the late Pleistocene loess of the Negev [Avni et al, 2006], but even these ages are on reworked, secondary fluvial loess and not primary loess.…”
Section: Loess In the Negev Desertmentioning
confidence: 99%
“…This in part is supported by the isotopic composition of fossil snails (Margaritz, 1986). The geomorphic and sedimentary records, however, indicate that this interval was somewhat wetter (Goldberg, 1986) characterized by alluvial aggradation in the Negev during the earlier half (Goldberg and Brimer, 1983) and by soil development (Goodfriend and Margaritz, 1988).…”
Section: Biostratigraphic Evidencementioning
confidence: 92%
“…In the central Negev, for example, Goldberg (1986) observed that Nahals Sekker and Besor preserve a sequence of continuous aggradation in the Late Pleistocene, rather than hemicycles of cut-fill. Bull and Schick (1979), working in the southern Negev, concluded that sediment yields and alluviation increased under hyperarid conditions late in the Pleistocene and that subsequent entrenchment occurred in the Holocene.…”
Section: Climate and Sedimentary Sequencesmentioning
confidence: 96%
See 1 more Smart Citation
“…A revision of Vita-Finzi's original model included a more complex chronology based on four alluvial fills (Copeland and Vita-Finzi, 1978), although it still proved too simplified to apply to all Jordanian wadis. Criticism of this model arose in several regions of the Mediterranean as more accurate dating suggested more complex fluvial histories (Goldberg, 1986;Van Andel et al, 1990;Mabry, 1992;Schuldenrein and Clark, 1994;Grove, 1997).…”
Section: Introductionmentioning
confidence: 98%